The rural immersion program of the Civil Service Academy - Astillero, Emmanuel I. (Philippine Journal of Public Administration, 1980)
Rural Immersion is one part of the training modules of the Civil Service Academy focused on the Executive Leadership Management (ELM) Program. Its goal is to infuse managerial expertise in the participants even as they develop a high sense of commitment toward the improvement of the quality of life of the rural poor. This training module is divided into four components, viz.: the pre-departure briefing, the barangay immersion, the case history and project proposal, and the debriefing and critique. In the light of incongruent orientations between the change agents and the target clientele of development the burden of effecting changes in the lives of the rural community rests upon the ELM graduates.